2004
DOI: 10.1021/es035288h
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Trends and Spatial Distributions of Brominated Flame Retardants in Archived Fishes from the Great Lakes

Abstract: To explore the geographical distribution and temporal trends of polybrominated diphenyl ethers (PBDEs) in the Great Lakes, lake trout from Lakes Superior, Michigan, Huron, and Ontario and walleye from Lake Erie, collected during the period of 1980−2000, were analyzed. The concentrations of fifteen PBDE congeners and one polybrominated biphenyl (PBB-153) were determined in each fish sample. Lake trout from Lakes Michigan and Ontario had the highest ∑PBDE concentrations during the years investigated. The ∑PBDE c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
162
10
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(196 citation statements)
references
References 17 publications
23
162
10
1
Order By: Relevance
“…Therefore, the results of the present study were displayed in another way (pg/g lw). As listed in Table 1, levels of PBBs (424-1142 ng/g lw in the present study) were significantly greater than those (\100 ng/g lw for PBB 153) in fish tissues from the Great Lakes (Zhu & Hites 2004). This result once again proved the heavy contamination of HOPs in the e-waste site.…”
Section: Pbbs Pbdes and Oh-pbdessupporting
confidence: 67%
“…Therefore, the results of the present study were displayed in another way (pg/g lw). As listed in Table 1, levels of PBBs (424-1142 ng/g lw in the present study) were significantly greater than those (\100 ng/g lw for PBB 153) in fish tissues from the Great Lakes (Zhu & Hites 2004). This result once again proved the heavy contamination of HOPs in the e-waste site.…”
Section: Pbbs Pbdes and Oh-pbdessupporting
confidence: 67%
“…Kajiwara et al (2004) observed an apparent decrease in concentration in the fur seal from 1994 to 1998 and Sellstrom et al (2003) observed a significant decrease from the mid 1980s to 2001 in guillemot eggs from the Baltic Sea. These recent decreases are likely the result of changes in industrial practices and/or regulations in Europe and Japan that have gradually controlled the use of PBDEs, especially penta-BDE (Zhu and Hotes, 2004).…”
Section: Temporal Variationmentioning
confidence: 99%
“…While rapid monitoring of aqueous PPCP contaminants is of high interest to environmental protection, the ability to quantify these species is necessary in assessing remediation efforts [4] and establishing geographical and temporal trends of contaminant plumes [39]. Figure 4b shows a calibration curve generated from tap water solutions of citalopram, ranging from the limit of quantitation (LOQ) of 20 ppt to 7500 ppt.…”
Section: Quantitation and Optimization Of Sample Flow Ratementioning
confidence: 99%